Effectiveness of an Enhanced Community Doula Intervention in a Safety Net Setting: A Randomized Controlled Trial (Mary Ann Liebert, 2023)
Background: Racial inequities in maternal health outcomes, the result of systemic racism and social determinants of health, require maternity care systems to implement interventions that reduce disparities. One such approach may be support from a community doula, a health worker who provides emotional support, peer education, navigation, and advocacy for pregnant, birthing, and postpartum people who share similar racial identities, cultural backgrounds, and/or lived experiences. While community support during birth has a long tradition within communities of Black Indigenous and People of Color (BIPOC), the reframing of community doula support as a social intervention that reduces disparities in clinical outcomes is recent. Methods: We conducted a pragmatic randomized trial at an urban safety net hospital, comparing standard maternity care with standard care plus enhanced community doula support. We tested the effectiveness of a community doula program embedded in a safety net hospital in improving birth outcomes and explored the association between community doula support and health equity. Participants were nulliparous, insured by publicly funded health plans, and had lower risk pregnancies. The primary outcome was cesarean birth. Secondary outcomes included preterm birth and breastfeeding outcomes. Exploratory subgroup analysis was conducted by race?ethnicity. Results: Three hundred sixty-seven participants were included in the primary analysis. In the intent-to-treat analysis, outcomes were similar between groups. There was a trend toward increased breastfeeding initiation (p=0.08). There was a statistically nonsignificant 12% absolute reduction in cesarean birth and 11.5% increase in exclusive breastfeeding during delivery hospitalization among Black non-Hispanic participants. Discussion: While outcomes for the study sample were similar between randomization groups, health outcomes were improved for Black birthing people in cesarean and breastfeeding rates. Conclusion: This study demonstrates the need for larger studies of community doula support for Black birthing people. Clinicaltrials.gov ID: NCT02550730.